Edukasi Postur Tubuh yang Baik dan Benar Saat Duduk pada Komunitas Remaja di SMPK Santo Yusup 2 Malang - Khoirunna'im, Vika; Nungki Marlian Yuliadarwati; Eleonora Elsa Sucahyo (Health Care : Journal of Community Service, 2025)
Educating students about proper body posture while sitting is an important aspect of maintaining physical health, especially in the school environment. This study aims to provide an understanding of good and ideal sitting posture to students at SMPK Santo Yusup 2 Malang. The method used is an educational approach through seminars and visual aids such as posters and PowerPoint presentations, where students are taught the impact of poor sitting posture and how to arrange their sitting position correctly. Evaluation results showed an increase in students' knowledge about proper body posture, evidenced by post-test results from questionnaires completed by students after receiving the material, and changes in behavior regarding maintaining correct sitting positions. Thus, this educational activity not only contributes to students' physical health but can also enhance concentration and learning productivity. It is hoped that this counseling can become a reference for other educational institutions in implementing similar programs.